Elucidation of the biogenesis of the paraherquamides, malbrancheamides, citrinalins, and brevianamides - Klas, Kimberly R., author; Williams, Robert M., advisor; Shi, Yian, committee member; Chen, Eugene, committee member; Crick, Dean, committee member (Colorado State University. Libraries, 2019)
Various fungi of the genera Aspergillus, Penicillium and Malbranchea produce prenylated indole alkaloids that possess a bicyclo[2.2.2]diazaoctane ring system and a variety of biological activities such as insecticidal, cytotoxic, anthelmintic, and antibacterial properties. After the discovery of distinct enantiomers of the natural alkaloids Stephacidin A, Notoamide B and their corresponding diastereomers, from Aspergillus protuberus MF297-2, Aspergillus amoenus NRRL 35660 and Aspergillus taichungensis, the structurally diverse metabolites became of particular biosynthetic interest. The bicyclo[2.2.2]diazaoctane core of the divergent natural metabolites may be enzymatically derived via a putative intramolecular hetero-Diels-Alder cycloaddition. We completed the total synthesis of ZwtP and MeZwtP, unveiling the role of a newly discovered Diels-Alderase. We are also undergoing further synthetic efforts to access other novel natural products, as well as further understand additional unprecedented transformations in nature.
Keywords: citrinalin; natural products; ZwtP; Diels-Alderase; brevianamide; prenylated indole alkaloids